Axillary nodal metastatic burden in patients with breast cancer with clinically positive axillary nodes. Issue 12 (3rd June 2020) - Niinikoski, L; Hukkinen, K; Leidenius, M H K; Heikkilä, P; Mattson, J; Meretoja, T J
Abstract: Background: The aim of this study was to determine preoperative factors and tumour characteristics related to a high nodal tumour burden in patients with clinically node-positive breast cancer. These findings were used to construct a predictive tool to evaluate the patient-specific risk of having more than two axillary lymph node metastases. Methods: Altogether, 507 consecutive patients with breast cancer and axillary lymph node metastasis diagnosed by preoperative ultrasound-guided needle biopsy were reviewed. These patients underwent breast surgery and axillary lymph node dissection at Helsinki University Hospital between 2010 and 2014. Patients were grouped into those with one or two, and those with more than two lymph node metastases. Results: There were 153 patients (30·2 per cent) with one or two lymph node metastases and 354 (69·8 per cent) with more than two metastases. Five-year disease-free survival was poorer for the latter group ( P =  0·032). Five-year overall survival estimates for patients with one or two and those with more than two lymph node metastases were 87·0 and 81·4 per cent respectively ( P =  0·215). In multivariable analysis, factors significantly associated with more than two lymph node metastases were: age, tumour size, lymphovascular invasion in the primary tumour, extracapsular extension of metastasis in lymph nodes, and morphology of lymph nodes. These factors were included in a multivariable predictive model, which had an area under the curve of 0·828 (95 per cent c.i. 0·787 to 0·869). Conclusion: The present study provides a patient-specific prediction model for evaluating nodal tumour burden in patients with clinically node-positive breast cancer. Graphical Abstract: Factors related to having more than two lymph node metastases in patients with clinically node-positive breast cancer were younger age, larger size and lymphovascular invasion of the primary tumour, extracapsular extension of lymph node metastases, and lymph node morphology on ultrasonography (more than 1 suspicious lymph node). A well performing patient-specific prediction model for evaluating nodal tumour burden in patients with clinically node-positive breast cancer was developed. Institutional validation is needed before its application in clinical practice at other institutes. Less axillary surgery for many